Pembangunan Ekonomi Berkelanjutan Dan Daya Dukung Lingkungan Berbasis Jejak Ekologis Di Negara Asean - Egi Destiani; Zulfa Emalia (Departement of Mathematics Education, 2024)
Ecological footprint is one of the indicators that can be used to see the condition of environmental carrying capacity and sustainable economic development. The aim of this research is to analyze the long-term influence of GDP per capita, trade openness and energy consumption on the ecological footprint in ASEAN countries. Secondary data used in this research was obtained from official information sources, namely the Global Footprint Network (GFN), the World Bank, and Our World in Data. The analytical method used in this research is Fully Modified Ordinary Least Square (FMOLS) and uses panel data with a total of 160 data in the research period 2000-2019. The research results show that the variables GDP per capita, trade openness and energy consumptionon have a positive and significant influence in the long term on the eological footprint in ASEAN countries.